White Matter Hyperintensities, Dopamine Loss, and Motor Deficits in De Novo Parkinson's Disease. Issue 6 (29th January 2021) - Jeong, Seong Ho; Lee, Hye Sun; Jung, Jin Ho; Baik, Kyoungwon; Lee, Yang Hyun; Yoo, Han Soo; Sohn, Young H.; Chung, Seok Jong; Lee, Phil Hyu
Abstract: Background: White matter hyperintensities, prevalent in patients with Parkinson's disease (PD), significantly affect parkinsonian motor symptoms. The objective of this study was to investigate the relationship between white matter hyperintensities and nigrostriatal dopamine depletion and their interaction or mediating effects on motor symptoms in patients with drug‐naive early‐stage PD. Methods: This cross‐sectional study enrolled 501 patients with de novo PD who initially underwent [ 18 F] N‐(3‐fluoropropyl)‐2β‐carbonethoxy‐3β‐(4‐iodophenyl) nortropane positron emission tomography and brain magnetic resonance imaging scans between April 2009 and September 2015 in a tertiary‐care university hospital. We quantified dopamine transporter availability in each striatal subregion and assessed the severity of periventricular and lobar white matter hyperintensities using the Scheltens scale. The relationship between white matter hyperintensities, dopamine transporter availability in the posterior putamen, and Unified Parkinson's Disease Rating Scale (UPDRS) motor scores was assessed using multivariate linear regression and mediation analyses. Results: Periventricular and frontal white matter hyperintensities were generally associated with dopamine transporter availability in striatal subregions after adjusting for age at symptom onset, sex, disease duration, and vascular risk factors. There was an interaction effect between periventricular white matter hyperintensities and dopamine transporter availability in the posterior putamen for the axial motor score. The effect of white matter hyperintensities on UPDRS total score and bradykinesia subscore was indirectly mediated by dopamine transporter availability in the posterior putamen, whereas the axial sub‐score was directly affected by white matter hyperintensities. Conclusions: This study suggests that the detrimental effect of white matter hyperintensities on parkinsonian motor symptoms is more relevant and independent for axial motor impairments in the status of mildly decreased striatal dopamine transporter availability. © 2021 International Parkinson and Movement Disorder Society